FBH1 mediates DNA double strand breakage and apoptosis in response to DNA replication stress - Jeong, Yeon Tae (2013)
Proper resolution of stalled replication forks is essential for genome stability. Purification of FBH1, a UvrD DNA helicase, identified a physical interaction with replication protein A (RPA), the major cellular singlestranded DNA (ssDNA)?binding protein complex. Compared with control cells, FBH1-depleted cells responded to replication stress with considerably fewer double-strand breaks (DSBs), a dramatic reduction in the activation of ATM and DNA-PK and phosphorylation of RPA2 and p53, and a significantly increased rate of survival. A minor decrease in ssDNA levels was also observed. All these phenotypes were rescued by wild-type FBH1, but not a FBH1 mutant lacking helicase activity. FBH1 depletion had no effect on other forms of genotoxic stress in which DSBs form by means that do not require ssDNA intermediates. In response to catastrophic genotoxic stress,  apoptosis prevents the persistence and propagation of DNA lesions. Our findings show that FBH1 helicase activity is required for the efficient induction of DSBs and apoptosis specifically in response to DNA replication stress.